The Crystal Structure of the Ca2+-ATPase 1 from Listeria monocytogenes reveals a Pump Primed for Dephosphorylation. Issue 16 (6th August 2021) - Hansen, Sara Basse; Dyla, Mateusz; Neumann, Caroline; Quistgaard, Esben Meldgaard Hoegh; Andersen, Jacob Lauwring; Kjaergaard, Magnus; Nissen, Poul
Graphical abstract: Highlights: Crystal structures of Listeria Monocytegenes Ca 2+ -ATPase LMCA1 in calcium-free E2 forms. LMCA1 has only a single calcium site. LMCA1 adopts the same outward-closed/occluded conformation in all structures. The TGES loop pre-activates LMCA1 for dephosphorylation. Insertion of four glycines in the A-M1 linker affects structural transitions. Abstract: Many bacteria export intracellular calcium using active transporters homologous to the sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA). Here we present three crystal structures of Ca 2+ -ATPase 1 from Listeria monocytogenes (LMCA1). Structures with BeF3 - mimicking a phosphoenzyme state reveal a closed state, which is intermediate between the outward-open E2P and the proton-occluded E2-P* conformations known for SERCA. It suggests that LMCA1 in the E2P state is pre-organized for dephosphorylation upon Ca 2+ release, consistent with the rapid dephosphorylation observed in single-molecule studies. An arginine side-chain occupies the position equivalent to calcium binding site I in SERCA, leaving a single Ca 2+ binding site in LMCA1, corresponding to SERCA site II. Observing no putative transport pathways dedicated to protons, we infer a direct proton counter transport through the Ca 2+ exchange pathways. The LMCA1 structures provide insight into the evolutionary divergence and conserved features of this important class of ion transporters.